IDENTIFIKASI DAERAH RAWAN LONGSOR DI KECAMATAN CAMBA KABUPATEN MAROS MENGGUNAKAN MIKROTREMOR - Nirmayanti, Nirmayanti; Rahmaniah, Rahmaniah; Zelviani, Sri (JFT: Jurnal Fisika dan Terapannya, 2017)
A study entitled Identification of Landslide-Prone Areas in Camba Sub-District, Maros Regency Using Microtremor has been carried out. Microtremor is ground vibration other than earthquake, it can be a vibration due to human activities and natural activities. So microtremor can occur due to vibrations due to people who are walking, car vibrations, vibrations of factory machines, wind vibrations, ocean waves or natural vibrations from the ground. This study aims to determine how much the dominant frequency produced in microtremor measurements in landslide prone areas in Camba sub-district, Maros district. Data collection was carried out by 10 points. The data obtained were processed using geopsy software. Based on the research that has been carried out, it can be concluded that the measurement point that has the biggest landslide potential is at the measurement point that has the smallest dominant frequency value with a large dominant frequency of 0.73 Hz and the measurement point that has the smallest landslide potential is at the measurement point that has a value the largest dominant frequency with a dominant frequency of 8.27 Hz. The most dominant frequency value that appears is 5 Hz.